Using Videoconferencing to Provide Mentorship in Inquiry-Based Urban and Rural Secondary Classrooms - Qing Li; Patti Dyjur; Natalya Nicholson; Lynn Moorman (Canadian Journal of Learning and Technology, 2010)
The main purpose of this design-based research study is to examine the effects of an inquiry-based learning environment, with the support of videoconferencing, on both rural and urban secondary students’ mathematics and science learning. An important aspect of this learning environment is the use of videoconferencing to connect classes with mathematicians/ scientists (as e-mentors). Specifically, the following two research questions guide this study: (1) In what ways, if any, does the inquiry-based learning environment impact student beliefs and learning outcomes? (2) What challenges emerge in the development of an inquiry-based learning environment with secondary students in both rural and urban schools? Using a mixed methods approach, this study focuses on two grade 9 classes in an urban school and three Grade 8 classes in a rural school. The results suggest positive effects of this learning environment on student learning of math and science. In particular, both urban and rural students showed significant gains in their achievement. In addition, students showed an increased interest and heightened confidence in math and science. As well, the results point to issues arising from the process, suggesting useful guidelines for the development of such environments.